Minat Transaksi Daring Melalui Jasa Transportasi GO-JEK: Kepercayaan, Kemudahan Transaksional, Pemahaman Risiko Dan Kualitas Layanan - Shinta Permata Sari; Satria Pinandita; Himmatus Sholikhah (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2019)
The ease of internet use makes all activities more efficientto accomplish. Customers can fulfill their needs by utilizing onlineapplication. The purpose of this study is to find out the effect of trust, transactional ease, risk understanding and service quality to online-transaction interest. GO-JEK’s online transportation become the observed entity because GO-JEK is one of fast growth local companyin Indonesia. The study is conducted on the students at Economic andBusiness Faculty of Universitas Muhammadiyah Surakarta.The sampling methods of this study is convienence sampling methods.Data are collected by survey with questionnaires. 304 students arebeing respondents in this study. The data analyze using multiplelinear regression and the results show that trust and transactionalease have effect on online-transaction interest, whereas risk understanding and service quality have no effect on online-transaction interest.